2016
DOI: 10.1016/j.molmet.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue glycogen accumulation is associated with obesity-linked inflammation in humans

Abstract: ObjectiveGlycogen metabolism has emerged as a mediator in the control of energy homeostasis and studies in murine models reveal that adipose tissue might contain glycogen stores. Here we investigated the physio(patho)logical role of glycogen in human adipose tissue in the context of obesity and insulin resistance.MethodsWe studied glucose metabolic flux of hypoxic human adipoctyes by nuclear magnetic resonance and mass spectrometry-based metabolic approaches. Glycogen synthesis and glycogen content in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 69 publications
8
43
0
1
Order By: Relevance
“…These previous findings highlight the importance of our discovery that glycogen synthase (GYS1), the key biosynthetic enzyme for the synthesis of glycogen (103), is enriched in the SOGA1 interactome. While the role of glycogen autophagy in adipocytes was only recently examined (104), it is possible to hypothesize that SOGA1 may regulate glucose and glycogen metabolism by directly cooperating with glycogen synthase and the glycogen synthase-associated protein glycogenin, which was also detected in the SOGA1…”
Section: Discussionmentioning
confidence: 99%
“…These previous findings highlight the importance of our discovery that glycogen synthase (GYS1), the key biosynthetic enzyme for the synthesis of glycogen (103), is enriched in the SOGA1 interactome. While the role of glycogen autophagy in adipocytes was only recently examined (104), it is possible to hypothesize that SOGA1 may regulate glucose and glycogen metabolism by directly cooperating with glycogen synthase and the glycogen synthase-associated protein glycogenin, which was also detected in the SOGA1…”
Section: Discussionmentioning
confidence: 99%
“…To prevent spontaneous differentiation, primary cultures of ASCs at passage 0 (P0) were grown to 90% confluence and harvested with trypsin-EDTA, and aliquots (1 × 10 6 cells) were cryopreserved in liquid nitrogen until required ( Pachon-Pena et al., 2011 ). ATMs were also isolated from the stromal vascular fraction of AT biopsies as described previously ( Ceperuelo-Mallafre et al., 2016 , Serena et al., 2016 , Titos et al., 2011 ). The AT-cell number ratio was defined as the ratio of the number of cells proliferating at P0 per gram of AT digested.…”
Section: Methodsmentioning
confidence: 99%
“…Glycogen is an important carbohydrate fuel reserve and glycogen metabolism has been previously reported in myeloid cells of the immune system including dendritic cells and macrophages [14][15][16] . Our recent studies additionally found that CD8 + memory T cells actively mobilize glycogen metabolism to generate glucose-6-phosphate (G6P) via glycogenolysis and channel the G6P to the PPP 17 .…”
mentioning
confidence: 99%